2009
DOI: 10.1210/jc.2008-0834
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Epicardial Adipose Tissue Measured by Multidetector Computed Tomography to Components of the Metabolic Syndrome Are Region-Specific and Independent of Anthropometric Indexes and Intraabdominal Visceral Fat

Abstract: A simple measurement of EAT thickness in the left atrioventricular groove may provide a more accurate assessment of metabolic risk associated with EAT, which could not be accounted for by anthropometric indexes and intraabdominal visceral fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 29 publications
8
100
2
2
Order By: Relevance
“…In agreement with previous autopsy studies, or studies using Cardiac adiposity and heart function in obesity B Gaborit et al echography or computed tomography, EFV increases with age, BMI and waist circumference. 15,16,37,42 Surprisingly, EFV was not correlated with LV mass or EDV. Previous studies showed similar results.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In agreement with previous autopsy studies, or studies using Cardiac adiposity and heart function in obesity B Gaborit et al echography or computed tomography, EFV increases with age, BMI and waist circumference. 15,16,37,42 Surprisingly, EFV was not correlated with LV mass or EDV. Previous studies showed similar results.…”
Section: Discussionmentioning
confidence: 90%
“…The relative importance of VAT or EFV in the prediction of metabolic syndrome is a matter of debate. 16,31 Computed tomography measurement of EF thickness in the left atrioventricular groove was proposed as a more accurate assessment of metabolic risk than VAT. 16 A recent study by Iozzo et al 31 in 53 subjects, separated according to glucose tolerance, reported that pericardial fat and myocardial fat were independently related to plasma glucose levels, but the authors did not account for VAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Many studies have concluded that EAT is higher in the patients with diabetics, HT and obesity. [6][7][8][21][22][23] DM and HT are closely related with the metabolic syndrome and the two most frequently observed reasons of the increased cardiovascular risk in the general population and the ESRF patients. No study has been recorded yet which addresses uremic factors and its relationship with EAT in the dialysis patients without DM and HT.…”
Section: Discussionmentioning
confidence: 99%